Every picture tells a story : a location workshop with Steve Kossack. - Kossack, Steve (Master photo workshops., 2009)
"Experience a private photography workshop through the breathtaking scenery of northern Arizona with renowned landscape photographer and workshop leader Steve Kossack. Much more than just a collection of photography tips, watch and learn as Steve photographs the iconic beauty of Horseshoe Bend, Lower Antelope Canyon, and The Wave. In this photography video, Steve will inspire and enlighten viewers on the techniques he has perfected, allowing him to create the stunning landscape imagery he has become so well known for capturing. 'Every Picture Tells A Story' is about the journey of learning photography."--Resource description page.